Структура нанокристаллических покрытий ti-al-n - Тимченко Н. А. Николай Алексеевич; Коваль Н. Н. Николай Николаевич; Крысина О. В.; Галимов Р. М. Руслан Маликович; Шмаков А. Н. (2013, 2013)
Заглавие с экрана